Development and modification of TI02 based-nanophotocatalyst for direct conversion of C02 to hydrocarbon fuel - Azrina, Abd Aziz; Muzamir, Hasan; Che Ku Mohamad Faizal, Che Ku Yahya (2019)
Malaysia has huge coal reserves that can be fully tapped as an additional source of energy to lessen the burden of domestic industries currently saddled with increasingly high energy costs from gas and electricity. According to the Mineral and Geoscience Department, the country's coal resources are estimated at 1.72 billion tonnes, of which 274 million were measured, 347 million indicated and the balance 1.1 billion inferred. Even though coal is a national treasure, managing C02 emissions from its utilization is perhaps the largest technical challenge currently faced by the fossil energy industry. Although C02 is routinely captured from the conventional industrial processes includes ammonia production and limestone calcination, existing capture technologies are not economical for use in power plants. As such, transformational new technologies are needed to help and address the C02 challenges. Moreover most of the work on reducing the concentration of anthropogenic carbon dioxide in the atmosphere is focused on either reducing the emissions from fossil fuel combustion or capturing and sequestering the resulting carbon dioxide. There is, however, a third possible path: the conversion of C02 back to a hydrocarbon fuel.